Accumulation, tissue distribution, health hazard of microplastics in a commercially important cat fish, Silonia silondia from a tropical large-scale estuary - Hossain, M. Belal; Pingki, Farjana Haque; Azad, Md. Abdus Samad; Nur, As-Ad Ujjaman; Banik, Partho; Sarker, Pallab Kumer; Paray, Bilal Ahamad; Arai, Takaomi; Yu, Jimmy (Frontiers in Sustainable Food Systems, 2024)
The current knowledge regarding the presence of microplastics (MPs) in the digestive tracts of fish, particularly the non-edible parts, provides limited assistance in assessing the risk to human health and establishing guideline values for policy-making purposes. Therefore, we conducted the first investigation into MPs within the commercially significant catfish species S. silondia, form a major tropical estuary assessing their accumulation, characteristics, and associated risks in various tissues, particularly the consumable muscle. A sum of 132 MPs were identified, and the mean abundance of MPs were 7.40 ± 4.12 item/DT, 3.20 ± 1.69 item/gill and 2.60 ± 1.65 item/muscle found in digestive tract (DT), gill and muscle of the fish, respectively. The strong relationships of MPs among three different tissues (y = 0.6069x - 22.69, R2 = 0.7589) indicated the pathways and how MPs were influenced by the physiology of organisms. The prevalence of MPs in fish muscle demonstrated their trophic transmission to humans. Moreover, fishes with higher weight had higher MPs in their gill, and DT. The dominant type, color and size of MPs were fibrous (89.67%), violet (41%) and < 0.5 mm sized (94%), respectively. The high percentage of fibers suggests that they might have come from ropes, fishing nets or sewage. FTIR chemical composition analyses of microplastics (MPs) identified three primary polymer types: PET (44.5%), PE (33.3%), and PP (22.2%) in fish. These polymers are commonly associated with packaging materials, household wastes and plastic pipes. Contamination level assessment by CF (CF = 2.76) and PLI (PLI > 1) indicated moderately to highly contaminated fish with MPs ingestion. While the complete understanding of the direct negative effects of microplastics (MPs) on human health remains elusive, their presence in estuarine fish raises concerns for both human and ecosystem health. The findings will be useful for assessing the hazards to human health from exposure to MPs and for creating effective risk management plans to reduce those risks.